An intelligent diagnostic system for diabetes using rule based reasoning and object-oriented methodology - Balakrishnan, Vimala; Govindan, Vithyatheri (2011)
Diabetes is one of the most prevalent chronic diseases with many short and long term complications. This paper presents an intelligent diagnostic system specifically developed for Type 1 and Type 2 diabetes, using rule-based reasoning and object-oriented methodology. The system accurately diagnoses Type 1 and Type 2 diabetes based on the sign-symptoms entered, and also provides an explanation to reasoning. We believe that great improvements can be provided to the medical practitioners and also the diabetics with the implementation of this system.